POTRET REMAJA TERLANTAR: STUDI KASUS PADA PANTI SOSIAL BINA REMAJA (PSBR) - Nurdin Widodo (Sosio Konsepsia, 2010)
Study of neglected adolescence profile shows the description of related aspects which as main cause of the neglect then served in PSBR. The study was conducted in PSBR that managed by the Ministnj of Social Affairs and Provincial Office. Both of those samples were decided purposively. Based on those criteria, the sample chosen were PSBR in West Sumaiera, Riau, East Java and South Sulawesi. In each province selected 2 PSBR which managed by provincial offices, except Riau that only 1 PSBR that managed by the Ministry of Social Affairs. The study is descriptive-quantitative. The respondent includes ex client, management and staff of PSBR. The research found that the main cause of neglect are: 1) the fragile of harmony in the family, 2) weakness of control and social support, 3) less of knowledge and skill, and 4) impact of poverty.